2019
DOI: 10.1158/1535-7163.mct-18-1313
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Cell-Type Selective Antibody Internalization by a Guide-Effector Bispecific Design

Abstract: Cell-type-specific intracellular payload delivery is desired for antibody-based-targeted therapy development. However, tumor-specific internalizing antigens are rare to find, and even rarer for those that are expressed at uniformly high levels. We constructed a bispecific antibody that is composed of a rapidly internalizing antibody binding to a tumor-associated antigen, ephrin receptor A2 (EphA2), and a noninternalizing antibody binding to a highly expressed tumor-associated antigen, activated leukocyte cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…That excludes the efficient recycling back to the membrane, which has for instance been described for HER2-targeted ADC Kadcyla [30]. This is in line with other studies, including one study in which surface depletion of the fast internalizing target antigen is observed [28]. This may also be an explanation for the stabilization of the intracellular accumulation we observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…That excludes the efficient recycling back to the membrane, which has for instance been described for HER2-targeted ADC Kadcyla [30]. This is in line with other studies, including one study in which surface depletion of the fast internalizing target antigen is observed [28]. This may also be an explanation for the stabilization of the intracellular accumulation we observed.…”
Section: Discussionsupporting
confidence: 91%
“…An interesting observation is that addition of a slow internalizing sdAb to a fastinternalizing sdAb led to an even faster internalizing sdAb construct, biparatopic 4A10-3G7. In a recent study, a fast internalizing single-chain variable fragment (scFv) fused to a non-binding antibody was rendered slow internalizing by substitution of the non-binding antibody for a slow-internalizing antibody [28]. Based on this example, one could expect that the biparatopic sdAb construct would internalize slower than 4A10 alone.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Lee and colleagues [140] has shown that using ADC (antibodydrug conjugate) approaches by producing a bispecific designed antibody conjugate of anti-EphA2 and anti-ALCAM was able to trigger a rapid internalisation of the conjugate at the particular ratio. An interesting observation is that when the ADC conjugated with a toxic drum (MMAF, Monomethyl auristatin F), the ADC-drug produced some impressive toxicity in cells that expressed a high level of ALCAM [140]. This is an interesting approach, although the overall impact of targeting/internalising ALCAM itself on the fate of a cell and potentially in the body yet have to be fully assessed.…”
Section: Alcam As a Therapeutic Targetmentioning
confidence: 99%
“…This can either be a biologically active cytotoxic drug, or a cytotoxic radionuclide. A potential downside of using cytotoxic drugs is that they need to be internalized by the cancer cell and intracellularly released before they can perform their biological function on quickly dividing cells only [17], whereas utilizing targeted radionuclide therapy (TRNT) allows this radiopharmaceutical to exert its anti-tumor effect when bound to the cell surface by inducing DNA damage through radioactive decay. Depending on the travel distance of the emitted cytotoxic particle, more than one cancer cell can be targeted per decay event.…”
Section: The Problem Of the Brainmentioning
confidence: 99%